Determination of total phenol, antioxidant and antimicrobial activities of Avena sativa and Ocimum basilicum (Baghdad Science Journal, 2025)
The present study investigated the total content of phenolic compounds, antioxidant and antimicrobial activities of water extracts oat (Avena sativa) and basil (Ocimum basilicum), medicinal plants. The Folin-ciocalteu reagent assay was used to estimate the total phenolic content of plants extract. The antioxidant capacity of the plants extract was tested by ferric reducing/antioxidant power Assay (FRAP) and ferric reducing scavenging activity using DPPH method, and the antimicrobial activity was measured against [Staphylococcus epidermidis; Staphylococcus aureus; Proteus spp.; Klebsiella spp.; Escherichia coli; Candida albicans] as tester strains. The total phenolic content of Avena sativa and Ocimum basilicum extracts revealed that the mixture of plants showed higher content. The mixture of Avena sativa and Ocimum basilicum extracts showed the highest antioxidant capacity followed by Avena sativa extract and Ocimum basilicum extract with FRAP and DPPH assay. However, mixture of Avena sativa and Ocimum basilicum extracts exhibited the highest antimicrobial activity when compared to the other extracts. Thus the study revealed that the consumption of mixture herbs may enhance the immune power of our body against diseases due to free radicals.